The Effect of Using the Scramble Model on the Writing Skills of Seventh Grade Students at Nurul Iman Al-Barkah Islamic Middle School Tangerang - Rella Dita Mauldi; Ubaid Ridlo; Wati Susiawati (Penerbit Minhaj Pustaka, 2026)
The purpose of this study is to reveal the steps in using the Scramble model in teaching Arabic writing skills, as well as to examine the effectiveness of applying the Scramble model in students’ writing skills and to determine the improvement of seventh-grade students’ Arabic writing skills at this school after using the Scramble model. This research is a quantitative study that applies a Pre-Experimental design with one group, namely the experimental group, in the form of a one-group pretest-posttest design. The population and sample of the study consisted of 20 students. The data collection methods used were observation, interview, and written tests (pretest and posttest). The average score of the pretest was 37.05, while the posttest average was 75.8 in the experimental group. The researcher used a “t-test” to calculate the hypothesis, where the calculated t-value (t₀) was greater than the t-table (tt) at the 5% and 1% significance levels, with degrees of freedom determined using the formula (N-1). The result showed that (t₀) was 8.10, which exceeded (tt), meaning the alternative hypothesis (H₁) was accepted and the null hypothesis (H₀) was rejected. The effect size measurement using Cohen’s d test produced a value of 1.81, indicating a “very significant effect.” The researcher concluded that: (1) the use of the Scramble model had a significant effect on writing skills, and (2) the use of the Scramble model played an important role for students, as it helped improve their ability in Arabic writing skills.